2016
DOI: 10.1097/bpo.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Buddy Taping With a Short-Arm Splint and Operative Treatment for Phalangeal Neck Fractures in Children

Abstract: Buddy taping with a short-arm splint for treating phalangeal neck fractures had acceptable outcomes compared to that with surgical correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…More recently, most centers (including ours) have adopted a more conservative approach to minimally displaced fractures as long as there is no rotational deformity. 8,10 Our results support the conservative approach in minimally displaced type II D fractures.…”
Section: Discussionsupporting
confidence: 72%
“…More recently, most centers (including ours) have adopted a more conservative approach to minimally displaced fractures as long as there is no rotational deformity. 8,10 Our results support the conservative approach in minimally displaced type II D fractures.…”
Section: Discussionsupporting
confidence: 72%
“…Buddy taping for the treatment of finger fractures as an adjunct to protective splinting has been recommended in several studies (Figl et al, 2011;Fok et al, 2013;Franz et al, 2012Franz et al, , 2013Park et al, 2016;Pezzei et al, 1993;Rajesh et al, 2007). The combination of some of these splints with buddy taping allows early mobilization, and it has been demonstrated that this functional treatment prevents stiffening and therefore achieves free mobility and bony healing at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…It is very likely that they have treated not only sprains but also stable fractures by buddy splinting (Aitken and Court-Brown, 2008;Briner and Kacmar, 1997;Chen and Kalainov, 2017;Gaston and Chadderdon, 2012;Shaftel and Capo, 2014 Although buddy taping has been used since the seventies, it is only recently that buddy taping without supplementary splinting was introduced as a recognized treatment modality for fractures in the medical literature. Only a few studies, none of them prospective, have been published on the subject (Figl et al, 2011;Franz et al, 2012Franz et al, , 2013Loosli and Garrick, 1987;Park et al, 2016;Pezzei et al, 1993;Vadstrup et al, 2014). In 2009, buddy taping was recommended as a standard treatment for undisplaced, closed fractures of the proximal phalanx in the American Society for Surgery of the Hand Manual of Hand Surgery (Baltera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, outcomes of nonsurgical treatment for displaced phalangeal neck fractures are not well documented in literature. 9,10 This study was designed to investigate the radiological outcome of phalangeal neck fractures treated nonsurgically. In particular, we wanted to define whether, and by how much, these fractures displace over time.…”
mentioning
confidence: 99%